Autosomal Dominant Type II Osteopctrosis in an Asymptomatic Adolescent: A Case Report (TAJ: Journal of Teachers Association, 2009)
Osteopetrosis is a heterogeneous group of heritable conditions in which there is a defect in bone resorption by osteoclasts. The disease has variable mode of inheritance with variable expression of severity. We are reporting a 14 year old asymptomatic girl with autosomal dominant type II osteopetrosis and then the literature is reviewed.TAJ 2009; 22(1): 251-254